Lan tỏa rủi ro đuôi từ giá dầu thế giới đến thị trường chứng khoán các nước ASEAN-6 - Ngô Thái, Hưng; Nguyễn Khánh, An; Lê Phạm Thị Phương, Tiền; Trần Khánh, Vy; Nguyễn Thị Thanh, Trúc; Lê Như, Quỳnh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study aims to assess the tail risk spillovers from crude oil prices to the stock markets in ASEAN-6 countries (Vietnam, Thailand, Indonesia, Philippines, Malaysia, and Singapore) during the period 2017–2023. The DCC-GARCH model is employed to estimate CoVaR, ΔCoVaR, and the Kolmogorov-Smirnov test to evaluate and compare the magnitude of oil price risk spillovers on the ASEAN-6 stock markets. Empirical results reveal that tail risks from oil prices reduce the impact of risks on the ASEAN-6 stock markets over the sample period. Additionally, tail risk spillovers during the pre-COVID-19 and Russia-Ukraine conflict periods are relatively low across the selected countries. During the COVID-19 period, the ASEAN-6 stock markets experience higher risk spillovers from decreases in crude oil prices compared to other periods. Specifically, Vietnam, Thailand, and Indonesia are the three markets facing higher risk spillovers from oil prices in comparison to others. Policymakers and regulatory authorities should increase awareness, oversight, and action plans to minimize adverse oil risk effects.
Keywords: Oil prices; Stock markets; Systemic risks; ASEAN-6